A water-soluble membrane transporter for biologically relevant cations. Issue 43 (29th September 2022) - Yang, Kylie; Boles, Jessica E.; White, Lisa J.; Hilton, Kira L. F.; Lai, Hin Yuk; Long, Yifan; Hiscock, Jennifer R.; Haynes, Cally J. E.
Abstract : Synthetic ionophores are promising therapeutic targets, yet poor water solubility limits their potential for translation into the clinic. Here we report a water soluble, supramolecular self-associating amphiphile (SSA) with cation transport function. Abstract : Synthetic ionophores are promising therapeutic targets, yet poor water solubility limits their potential for translation into the clinic. Here we report a water-soluble, supramolecular self-associating amphiphile that functions as a cation uniporter in synthetic vesicle systems, deriving mechanistic insight through planar bilayer patch clamp experiments.